Former Glory and Challenges Ahead: The Definition of Working Life Research in Sweden - Håkansta, Carin (Nordic Journal of Working Life Studies, 2014)
This conceptual paper looks into the definition of “working life research” in Sweden and poses two questions: (1) How has the definition of the concept working life research changed over time? (2) Why has it changed? The paper is based on two studies using two different empirical sources. The first source consists of government documents related to science policy in general and working life research in particular. The second source consists of interviews with Swedish researchers. According to the results of the first study, there has been a gradual decrease in attention to working life research in government science science policy documents since the 1990s. Furthermore, there was a conceptual change in the early 1990s when working life research went from referring to work organization research to a broader definition also including work environment and labor market research. The results from the second study show that work science decreasingly appears in university curricula and in titles of university departments. They also show that currently active researchers, especially the younger ones, tend not to refer to themselves as “work scientists” and “working life researchers.” The author argues that the root cause of the apparent disappearance of the concept working life research has been the influence of neoliberalism, which, since the 1980s–1990s, has affected science policy as well as labor market policy. The effects of policy change on working life research are the loss of its previously so privileged position in the public science system and the weakening of what used to be its most important political ally: the trade unions.